Club Cell Loss as a Feature of Bronchiolization in ILD - Reynaud, Paul; Ahmed, Engi; Serre, Isabelle; Knabe, Lucie; Bommart, Sébastien; Suehs, Carey; Vachier, Isabelle; Berthet, Jean Philippe; Romagnoli, Micaela; Vernisse, Charlotte; Mallet, Jean Pierre; Gamez, Anne Sophie; et al. (Frontiers in Immunology, 2021)
Background: Distal airway metaplasia may precede honeycombing in progressive fibrosing interstitial lung disease (ILD). The SCGB1A1+ bronchiolar-specific club cell may play a role in this aberrant regenerative process. Objective: To assess the presence of club cells in the small airways of patients suffering from ILD. Methods: Small airways (internal diameter <2 mm) in lung samples [surgical lung biopsy (SLB) and/or transbronchial lung cryobiopsy (TBLC)] from 14 patients suffering from ILD and 10 controls were morphologically assessed and stained for SCGB1A1. SCGB1A1 was weighted by epithelial height as a marker of airway generation (SCGB1A1/EH). Correlations between clinical, functional, and high-resolution CT (HRCT) prognostic factors and histomorphometry were assessed. Results: Small airways from samples with ILD patterns were significantly less dense in terms of SCGB1A1+ cells [0.064 (0.020–0.172)] as compared to controls' sample's small airways [0.393 (0.082–0.698), p < 0.0001]. Usual interstitial pneumonia (UIP) patterns most frequently contained small airways with limited or absent SCGB1A1 expression (SCGB1A1/EH <0.025): UIP (18/33; 55%) as compared with non-UIP patterns (4/31; 13%) or controls (0/29; 0%): p < 0.0001. In addition, correlations with HRCT indicated a significant negative relationship between SCGB1A1 and bronchiectasis as a feature of bronchiolization (Rho −0.63, p < 0.001) and a positive relationship with both forced vital capacity (FVC) and Hounsfield unit (HU)-distribution pattern in kurtosis (Rho 0.38 and 0.50, respectively, both p < 0.001) as markers of fibrotic changes. Conclusion: Compared with controls, the small airways of patients with ILD more often lack SCGB1A1, especially so in UIP. Low densities of SCGB1A1-marked cells correlate with bronchiectasis and fibrotic changes. Further research investigating SCGB1A1 staining as a pathological feature of the bronchiolization process is merited.